(untitled) (Agro Productividad, 2022)
Objective: To evaluate the operation of the Fondo de Aseguramiento Ganadero and its effectiveness regarding predator attacks, through the perception of ranchers who operate in the area of influence of the Calakmul Biosphere Reserve. Design/Methodology/Approach: The communities were visited in order to contact and ask the permission of the ejido authorities, as well as to inform ranchers about the activities. The streets of the communities were randomly covered by our team and a survey was carried out with all the available producers. The snowball method was used to identify producers who have been impacted by predator attacks. Results: Seventy surveys were carried out with ranchers of 18 communities from the northern, central, and southern regions of the area of influence of the Calakmul Biosphere Reserve (RBC), from October 2019 to January 2020. All the interviewed ranchers have been impacted by predator attacks; however, only 27% of them have reported the attacks to the Seguro de Ataques por Depredadores (Predator Attacks Insurance, SAD) and have obtained a compensation for their losses. Eighty-eight percent of the ranchers have received an immediate answer from the technician in charge of the insurance. Fifty-six percent of the ranchers mentioned that SAD has beneficial effects, 28% said they are not aware of its potential benefits, and 13% think that SAD does not have beneficial effects. Study Limitations/Implications: Although producers who have requested the insurance were identified, many other producers who have been impacted by predator attacks have not reported them. In many cases, the producers hunt the predator. Hunting these predators is illegal; therefore, producers decided not to provide the required information. Findings/Conclusions: as.